Tex264 Binding to SNX27 Regulates Itgα5 Receptor Membrane Recycling and Affects Cell Migration. (4th July 2022) - Xu, Xiao-hui; Yang, Qian-wen; Yue, Chang-ling; Zhu, Yun-yi; Zhang, Zhao-huan
Abstract : Tex264 is an endoplasmic reticulum (ER) membrane protein that was recently demonstrated to act as an ER-phagy receptor under starvation conditions to mediate endoplasmic reticulum autophagy. However, how Tex264 functions in the central nervous system (CNS) and tumors is unclear. Here, we identified 89 proteins from the rat brain that may specifically interact with Tex264 and confirmed the interaction between sorting nexin 27 (SNX27) and Tex264 by coimmunoprecipitation and immunofluorescence. Our results indicated that Tex264 may promote recycling of membrane proteins from endosomes to the cell plasma membrane by recruiting SNX27 retromer vesicles. siRNA-mediated knockdown of TEX264 in HeLa cells did not affect cell proliferation but did significantly inhibit cell migration through a mechanism that may involve a reduction in SNX27-mediated Itg α 5 receptor membrane recycling. Results of this study helped identify potential binding Tex264 partners and provide insights into Tex264 functions in the CNS and in tumors.